1997
DOI: 10.1364/ol.22.000834
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a multilayer-coated, ion-etched laminar holographic grating in the 145–160-nm wavelength region

Abstract: The efficiency of an ion-etched laminar holographic grating was measured at near-normal incidence in the 14.5-16.0-nm wavelength range. The grating had an electron-beam-evaporated Mo/Si multilayer coating matched to the grating groove depth. The efficiency peaked at 16.3% in the first inside order at 15.12 nm and 15.0% in the first outside order at 14.94 nm. These are believed to be the highest efficiencies obtained to date from a multilayer-coated laminar grating at near-normal incidence in the EUV (lambda<30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…First order efficiencies of 16 % were reported by Kowaiski et.al. for a 2400 L/mm laminar grating with an almost ideal phase matching [10]. For Mo/Si multilayer blaze gratings on-blaze efficiencies of 13 % for an ion-beam etched grating at normal incidence and 32 % for a ruled grating at 45 deg were reported by Seely et.al.…”
Section: Introductionmentioning
confidence: 65%
“…First order efficiencies of 16 % were reported by Kowaiski et.al. for a 2400 L/mm laminar grating with an almost ideal phase matching [10]. For Mo/Si multilayer blaze gratings on-blaze efficiencies of 13 % for an ion-beam etched grating at normal incidence and 32 % for a ruled grating at 45 deg were reported by Seely et.al.…”
Section: Introductionmentioning
confidence: 65%
“…For over a decade we have pursued the goal of achieving high effective area in a normal-incidence instrument by using ultra-smooth holographic ion-etched gratings that have been coated with high-reflectance multilayers. 1 We have measured efficiencies in the range 5-16% with both laminar and blazed gratings at wavelengths between 100 and 300 Å, [2][3][4][5][6] and in the laminar case the groove efficiency of the underlying grating substrate now approaches the theoretical limit for the first order of 40.5%. 7 Moreover, we have shown that the dispersive characteristics of the grating are unchanged with the application of the multilayer, and in one case a diffraction limited resolving power of 14,000 was achieved.…”
Section: Introductionmentioning
confidence: 82%
“…The value for Grating 1 is close to the theoretical limit of 40.5% and is in good agreement with our highest published result of 34.1% at 151.2 Å for a multilayer-coated ion-etched laminar test grating, but in that case the density was only 2400 grooves/mm. [5][6] The good agreement between the shape of the witness flat reflectance profile and the shapes of profiles at most grating locations means that the derived groove efficiencies are insensitive to wavelength over the 225-245-Å range.…”
Section: Efficiency Measurementsmentioning
confidence: 88%
“…Since that time, considerable effort has been directed to the implementation of this idea at various wavelengths and angles of incidence. [17][18][19][20][21][22][23][24][25][26] Of particular interest has been the implementation of blazed gratings due to potentially high diffraction efficincies, [19][20][21][22][23] however, in practice, square-wave gratings had been found to deliver higher first-order efficiency. [24][25][26] This is due to superior substrate control that had been achieved in the past with square-wave gratings as compared to that achieved with blazed gratings.…”
Section: Spillermentioning
confidence: 99%